Assessment of explosive destruction technologies for specific munitions at the Blue Grass and Pueblo chemical agent destruction pilot plants (National Academies Press, 2009)
The Army's ability to meet public and congressional demands to destroy expeditiously all of the U.S. declared chemical weapons would be enhanced by the selection and acquisition of appropriate explosive destruction technologies (EDTs) to augment the main technologies to be used to destroy the chemical weapons currently at the Blue Grass Army Depot (BGAD) in Kentucky and the Pueblo Chemical Depot (PCD) in Colorado. The Army is considering four EDTs for the destruction of chemical weapons: three from private sector vendors, and a fourth, Army-developed explosive destruction system (EDS).